Ultrasonic S-Wave to Obtain Shear Modulus and Matrix Permeability of D'Euville Limestone. (6th May 2022) - Li, Guangquan; Miao, Yifang; Li, Ruoyu
Abstract : In this paper, velocity and attenuation of ultrasonic S-wave in a water-saturated rock are used for calculating shear modulus and matrix permeability of the rock, via a model improved from Biot theory. The model requires two inputs, i.e., the dry velocity of S-wave and the average distance of aperture representing pores, to yield phase velocity and the quality factor as functions of frequency. By fitting the predicted velocity and quality factor against the ultrasonically measured counterparts, the dry velocity of S-wave and the average distance of aperture are ascertained, which in turn yield shear modulus and matrix permeability, respectively. The modeling results on D'Euville limestone from France show that the specimen has shear modulus of 11.35 and 11.55 GPa (under differential pressures of 3 and 5 MPa, respectively) and matrix permeability of 0.0486 Darcy (under both differential pressures). The matrix permeability appears to be approximately one half of Darcy permeability.